Heavy metals in intermediate He-rich hot subdwarfs: the chemical composition of HZ44 and HD127493 - Dorsch, Matti; Latour, Marilyn; Heber, Ulrich (Astronomy & Astrophysics, 2019)
Context. Hot subluminous stars can be spectroscopically classified as subdwarf B (sdB) and O (sdO) stars. While the latter are predominantly hydrogen deficient, the former are mostly helium deficient. The atmospheres of most sdOs are almost devoid of hydrogen, whereas a small group of hot subdwarf stars of mixed H/He composition exists, showing extreme metal abundance anomalies. Whether such intermediate helium-rich (iHe) subdwarf stars provide an evolutionary link between the dominant classes is an open question.Aims. The presence of strong Ge, Sn, and Pb lines in the UV spectrum of HZ44 suggests a strong enrichment of heavy elements in this iHe-sdO star and calls for a detailed quantitative spectral analysis focusing on trans-iron elements.Methods. Non-local thermodynamical equilibrium model atmospheres and synthetic spectra calculated with TLUSTY/SYNSPEC were combined with high-quality optical, ultraviolet (UV), and far-UV (FUV) spectra of HZ44 and its hotter sibling HD127493 to determine their atmospheric parameters and metal abundance patterns.Results. By collecting atomic data from the literature we succeeded in determining the abundances of 29 metals in HZ44, including the trans-iron elements Ga, Ge, As, Se, Zr, Sn, and Pb and providing upper limits for ten other metals. This makes it the best-described hot subdwarf in terms of chemical composition. For HD127493 the abundance of 15 metals, including Ga, Ge, and Pb and upper limits for another 16 metals were derived. Heavy elements turn out to be overabundant by one to four orders of magnitude with respect to the Sun. Zr and Pb are among the most enriched elements.Conclusions. The C, N, and O abundance for both stars can be explained by the nucleosynthesis of hydrogen burning in the CNO cycle along with the stars' helium enrichment. On the other hand, the heavy-element anomalies are unlikely to be caused by nucleosynthesis. Instead diffusion processes are evoked, with radiative levitation overcoming gravitational settlement of the heavy elements.
Keywords: stars: abundances; stars: atmospheres; stars: individual: HZ 44; stars: individual: HD 127493; stars: evolution; subdwarfs